"Jurisprudence Beyond the State: An Analysis of Jihadist "Justice" in Yemen, Syria and Libya. (4th May 2023) - Cook, Joana; Haid, Haid; Trauthig, Inga
Abstract: The provision of law, order and justice are some of the most sacred responsibilities of the contemporary nation-state. However, non-state actors have frequently introduced their own jurisprudence, implementing courts and various forms of related law and order in broader attempts to implement governance. Yet, little research has examined the diverse contours of such jurisprudence, and how these aspects offer insights into how these groups vie for legitimacy, and how such jurisprudence helps them achieve their strategic aims. Examining AQAP in Yemen, HTS in Syria, and ISIS in Libya this article describes the implementation, scope and contours of jihadist jurisprudence.